(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Aspects of the use of interactive educational technologies that allow to increase educational efficiency in the course of teaching the topics of the zoology class of mammals of future biology teachers studying in higher educational institutions are highlighted.